Considerations in Questionnaire Development: A Review - Ipsita Mahapatra1 , Ramesh Nagarajappa2 , Dharmashree Satyarup3 , Sharmistha Mohanty1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
A fundamental part of good research is concerned with making sure that the design of the questionnaireaddresses the needs of research. After a proper administration of the questionnaire, a questionnaire constantlymeasures what it intends to measure thereby giving us confident results of a study. It has been documentedin several studies regarding Validity and Reliability, as an important source of measuring the accuracyand consistency of research instruments (especially questionnaires). But their measure is not observedto be practiced in developing countries among health plus social science researchers. This review articlecomprehensively explores and describes questionnaire design and measures to validate a questionnaireincluding its reliability testing.